Gastroprotective Effect of Combination of Hot Water Extracts of Licorice (), Pulasari Stem Bark (), and Sembung Leaf () Against Aspirin-Induced Gastric Ulcer Model Rats - Agung Endro Nugroho MSc, PhD; Agustin Wijayanti MSc; Mutmainah Mutmainah MSc; Rina Susilowati MD, PhD; Nuning Rahmawati MSc (Journal of Evidence-Based Complementary & Alternative Medicine, 2016)
Licorice ( Glycyrrhiza glabra ), Pulasari stem bark ( Alyxia reinwardtii ) and Sembung leaf ( Blumea balsamifera ) are traditionally used to treat gastrointestinal disorders. The aim of the study was to investigate gastroprotective effect of hot water extracts combination of those herbal against aspirin-induced gastric ulcer model in rats. The combination consisted of fixed doses of Licorice 273 mg/kg BW and Sembung leaf 457.5 mg/kg BW, and also consisted of Pulasari stem in various doses i.e. 100 mg/kg BW (first group), 200 mg/kg BW (second and sixth group) and 300 mg/kg BW (third group). The fourth grup rats received sucralfate 360 mg/kg BW. Ten minute after seven consecutive days of drug administration, the rats were induced with aspirin 450 mg/kg BW except sixth group rats. The fifth group rats only received aspirin without any protective agents. The number and area of gastric ulcers were evaluated macroscopically. Whereas, histopatological observation was used for evaluation of mucosal damage score, and the number of eosinophils and mast cells. In the study, herbal extracts combination markedly exhibited protective effects indicated by less number and smaller area of gastric ulcers in comparison to those of aspirin group ( P < 0.05). The score of mucosal damages were also decreased in herbal extracts combination groups. The number of eosinophils and mast cells of herbal combination groups were observed to be smaller than those of aspirin group ( P < 0.05). In conclusion, herbal combination of Licorice (Glycyrrhiza glabra), Pulasari stem bark (Alyxia reinwardtii) and Sembung leaf (Blumea balsamifera) is potential to develop as a gastroprotective agent.